2022
DOI: 10.3389/fevo.2022.995783
|View full text |Cite
|
Sign up to set email alerts
|

Genetic substructure of Guizhou Tai-Kadai-speaking people inferred from genome-wide single nucleotide polymorphisms data

Abstract: The genome-wide characteristics and admixture history of the Tai-Kadai-speaking populations are essential for understanding the population genetic diversity in southern China. We genotyped about 700,000 single nucleotide polymorphisms (SNPs) of 239 individuals from six Tai-Kadai-speaking populations residing in the mountainous Guizhou Province of southwestern China. We merged the genome-wide data with available populations and ancients in East and Southeast Asia to infer Tai-Kadai-speaking populations’ admixtu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 42 publications
2
0
0
Order By: Relevance
“…Ren et al genotyped six TK-speaking populations from Guizhou Province and found that Gelao and Dong people in the north of Guizhou harbored more Han-related ancestry than Dong, Zhuang, Bouyei, and Mulao people in the south. Our newly studied DZGL had a similar genetic profile to Gelao in northern Guizhou reported by Ren et al, and the newly studied KLD had a similar genetic profile to the previously reported Dong in southern Guizhou but not in northern Guizhou (Ren et al, 2022). Chen et al sampled and genotyped Guizhou Maonan people and found their ancestry primarily from Guangxi historical people and minor ancestry from Northeast Asians (Chen et al, 2022).…”
Section: Discussionsupporting
confidence: 83%
“…Ren et al genotyped six TK-speaking populations from Guizhou Province and found that Gelao and Dong people in the north of Guizhou harbored more Han-related ancestry than Dong, Zhuang, Bouyei, and Mulao people in the south. Our newly studied DZGL had a similar genetic profile to Gelao in northern Guizhou reported by Ren et al, and the newly studied KLD had a similar genetic profile to the previously reported Dong in southern Guizhou but not in northern Guizhou (Ren et al, 2022). Chen et al sampled and genotyped Guizhou Maonan people and found their ancestry primarily from Guangxi historical people and minor ancestry from Northeast Asians (Chen et al, 2022).…”
Section: Discussionsupporting
confidence: 83%
“…It suggested that the vast mountains and rivers in Southwest China might decelerate the westward expansion of the Southeast coastal rice-farming groups. Previous studies have shown a genetic substructure in Tai-Kadai populations in Guizhou mainly caused by the different proportions of the genetic components from the Yellow River millet-farming groups in the north [50]. In our study, the genetic differences in TBG were caused mainly by the different proportions of the genetic influences from the south.…”
Section: Discussionsupporting
confidence: 50%